Detección de factores de riesgo clínicos cardiovasculares en estudiantes de bachillerato de los colegios del cantón Machala en el año 2011 - Vicente Mendoza, Luis F. (2012)
Cardiovascular risk is considered the probability of health problems related to heart and blood vessels, one of the cardiovascular risk factors is obesity and overweight, die each year at least 2,8 million people adult as a result of overweight or obese.